GC-MS Analysis of Diospyros montana (Roxb.) Leaves: A Medicinal and Poisonous Plant - Poonam Yadav,; Swati Dubey Mishra,; Kesar Singh,; M.P. Goutam, (The Bioscan, 2024)
Diospyros montana (Roxb.) is a plant that contains significant levels of flavonoids, phenol, reducing sugars, terpenoids and other phytochemicals. This plant is belonging to the Ebenaceae family. This plant is known as Bistendu (Poisonous tendu) due to its dual medicinal and poisonous characteristics; hence, it was considered essential to understand its whole phytochemical profile. In the current investigation, metabolites in the methanolic extract of leaves from the D. montana (Roxb.) plant were thoroughly screened phytochemically using the GC-MS technique with an emphasis on forensics. The plant's fresh leaves methanolic extract contained 13major compounds and identified are Phenol, 4-ethenyl-2,6- dimethoxy- Sucrose, (E)-4-(3-Hydroxyprop-1- en-1-yl) -2-methoxyphenol, 4-((1E)-3-Hydroxy-1-propenyl)-2- methoxyphenol, Hexadecanoic acid, methyl ester, Pentadecanoic acid, 14-methyl-, methyl ester, n-Hexadecanoic acid, Phytol, Linoelaidic acid, Hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester, Octadecanoic acid, Octadecanoic acid, 2-(2- hydroxyethoxy)ethyl ester, Glycerol 1-palmitate, 9,12,15-Octadecatrienoic acid, (Z,Z,Z)-, 2H-1-Benzopyran-3,4-diol, 2- (3,4-dimethoxyphenyl)-3, 4-dihyd.Therefore, a thorough phytochemical evaluation of metabolites may be helpful to forensic toxicologists investigating cases of plant poisoning. Moreover, because of the existence of phytochemicals and bioactive substances leaves can be utilized as a novel potential source of pharmaceutical drugs. The plant’s leaves were chemically profiled using the GC-MS method